Transmitter Gelombang Frekuensi Radio (RF) FM Berbasis Raspberry Pi - Mustofa, Ali; Kusmaryanto, Sigit; Ambarwati, Rusli; Dwika Nanda, Bravy (FORTEI (Forum Pendidikan Tinggi Teknik Elektro Indonesia), 2022)
In recent years, technology in the telecommunications sector has developed rapidly, especially with the global situation encouraging the use of long-distance communications. One of these developments is the use of the Raspberry Pi, abbreviated as Raspi, as a substitute for conventional computers for receiving and transmitting FM radio signals. Raspberry Pi is a mini and portable computer that can be used as an alternative to conventional computers in general, such as the use of teleconference media, offices, Big Data, and as a video player with high resolution. The problem in using a computer as an FM radio signal transceiver system is its complex and expensive infrastructure. When compared to the Raspberry Pi 3 with a price range of IDR 500,000 - IDR 1,000,000, a transceiver system using conventional computers requires a computer in general at a price far exceeding the said price. Using Raspi makes it easy to transmit FM radio signals by simply coding through the Raspi terminal. In this study, the authors propose a transmitter system using a Raspberry Pi 3B+ which is connected to a dipole antenna at a working frequency of 100 – 101 MHz. Raspi is operated using the SSH protocol for remote desktops. The operating system used is Raspberry Pi OS with the use of a MAC computer (MAC OS) as a remote desktop. The results show that the Raspberry Pi device can be used to transmit FM radio signals at a frequency of 100 - 101 MHz. The dipole antenna tested using VNA (Vector Network Analyzer) with a length of 71 cm and a linear form can transmit a signal with a VSWR of 1.08 - 1.95:1 at a working frequency of 94.9 - 103.06 MHz and a return loss of -28.1 dBm at a frequency of 98.98 MHz.